Analysis of the Need for Medical Records Personnel Based on Workload Using the WISN Method in the Filling Section of Mitra Sejati Hospital in Medan - Yeyi Gusla Nengsih (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
Analysis of the medical record workload is very necessary in improving health services in a hospital. This aims to determine which workloads need to be streamlined. In addition, with the analysis or measurement of workloads, scientific evidence-based decision making can be made. Seeing the large role of medical records in health services in hospitals, it is necessary what things are needed to improve the best quality in medical record installations. The purpose of this study was to determine the need for medical record personnel based on the workload in the filling section of Mitra Sejati General Hospital Medan. This type of research is descriptive with a cross sectional approach with a population of 4 medical record officers. The place where the research was conducted was at Mitra Sejati General Hospital Medan because the hospital had problems regarding work requirements in the filling section.